Atuação da coordenação pedagógica junto aos professores da sala de recursos multifuncionais (SRM) da escola Presidente Costa e Silva: um relato de experiência - SILVA, Claudete Sales da (2020)
The purpose of this study is to understand the role and importance of pedagogical coordination in the teaching-learning process, from a work within an inclusive perspective in the school environment, as well as to identify the actions developed by the pedagogical coordination, together with the classroom teachers of multifunctional resources (SRM), aimed at the inclusion of students with disabilities at the Presidente Costa e Silva School. In order to obtain data that would serve as input, a research and intervention was conducted, which resulted in this experience report, the result of an experience lived by the author as a scholarship holder of the Institutional Program for Initiation to Teaching (PIBID) school, where the actions of the pedagogical coordination and the teachers of the multifunctional resource room (SRM) were monitored. Thus, according to the literature of the area and with observation period at the Costa e Silva School, the results showed that the role of pedagogical coordination and its importance for the development of a work within an inclusive perspective is to provide an environment of learning based on the formulation of pedagogical interventions that value respect and encourage the deconstruction of prejudices. Finally, the report showed that there is in the said school the development of training actions to teachers and students on the theme of inclusion, such as workshops and lectures, but that due to diverse factors, internal and external, these are still small actions, making clear that in order to promote inclusion in schools, it is not enough to formulate formations or carry out reforms, but it involves a set of actions and factors, individual and collective, that influence in this process, and without proper governmental and social support there is no way to fully develop a work of inclusion.